Leadership traits of primary school principals and their relationship to job satisfaction for physical education teachers in Baghdad / Rusafa II. (Journal of the College of Basic Education, 2022)
The four-door research department: The first part includes the definition of research, which includes the introduction of research, its importance, research, problem of research and research objectives, namely: - Identify the leadership features of the school principals in Baghdad / Rusafa second from the perspective of teachers. - Recognition of job satisfaction of teachers of physical education in Baghdad / Rusafa second from the point of view of teachers. - To identify the relationship between the leadership qualities of managers and the job satisfaction of teachers from the point of view of teachers. The second part covered research methodology and field procedures: The researcher used the descriptive method and the sample are the teachers of physical education in Baghdad / Rusafa.the second (135). The third section included presentation, analysis and discussion of the results of job satisfaction for physical education teachers in Baghdad / Rusafa II. Section IV included the main conclusions and recommendations.